Is Whistle-blowing Compatible with Employee Loyalty? - Varelius, Jukka (Journal of business ethics, 2009)
Whistle-blowing would appear to involve a conflict between employee loyalty and protection of public interest. Several business ethicists have, however, argued that this conflict is indeed merely apparent. According to the central argument to that effect, when the nature of employee loyalty is understood correctly, it becomes clear that whistle-blowing does not threaten employees’ loyalty to their employer. This is because blowing the whistle about one’s employer’s wrongdoing and being loyal to them serves the same goal, the moral good of the employer. In this article, I assess this philosophical argument for the conclusion that the moral problem of whistle-blowing is not real. I argue that the way of defending the view that whistle-blowing is not morally problematic is implausible.